Polyphenols and Polypeptides in Chinese Rice Wine Inhibit Homocysteine-induced Proliferation and Migration of Vascular Smooth Muscle Cells. Issue 6 (June 2016) - Meng, Liping; Liu, Longbin; Zhou, Changzuan; Pan, Sunlei; Zhai, Xiaoya; Jiang, Chengjian; Guo, Yan; Ji, Zheng; Chi, Jufang; Peng, Fang; Guo, Hangyuan
Abstract : Abstract: The beneficial effect of Chinese rice wine on atherosclerosis has been proved, but the exact components that have the cardiovascular protective effect are still unknown. This study aimed to explore the exact ingredients in Chinese rice wine that could inhibit homocysteine (Hcy)-induced vascular smooth muscle cell (VSMC) proliferation and migration. VSMCs were divided into 7 groups: control, Hcy (1 mmol/L), Hcy + oligosaccharide, Hcy + polypeptides, Hcy + polyphenols, Hcy + alcohol, and Hcy + Chinese rice wine. methyl thiazolyl tetrazolium (MTT) assay, Transwell chambers, and wound-healing assay were used to test the proliferation and migratory ability of the VSMCs. Western blot and gelatin zymography were used to investigate the expressions and activities of metal matrix proteinase 2/9 (MMP-2/9) and tissue inhibitor of metalloproteinase 2 (TIMP-2) in VSMCs. Polypeptides and polyphenols in the Chinese rice wine reduced the proliferation and migration ability of the VSMCs. Furthermore, they also decreased the expression and activity of MMP-2/9 but had no obvious impact on the expression of TIMP-2 in each group. This study further confirms that polypeptides and polyphenols in the Chinese rice wine could inhibit Hcy-induced proliferation and migration of VSMCs and maintain the balance between matrix metalloproteinases (MMPs) and TIMPs.